2019
DOI: 10.1016/j.celrep.2019.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Replication Fork Proteome Identifies BET Proteins as PCNA Regulators

Abstract: SUMMARY Identifying proteins that function at replication forks is essential to understanding DNA replication, chromatin assembly, and replication-coupled DNA repair mechanisms. Combining quantitative mass spectrometry in multiple cell types with stringent statistical cutoffs, we generated a high-confidence catalog of 593 proteins that are enriched at replication forks and nascent chromatin. Loss-of-function genetic analyses indicate that 85% yield phenotypes that are consistent with activities in DNA and chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 68 publications
14
87
0
Order By: Relevance
“…Decreased levels of these proteins in the proximity of replication forks may create an altered chromatin structure that negatively affects replication fork function or they may be directly involved in replisome function. Indeed, it was recently shown that Brd2, Brd3 and Brd4 function at the replication fork to antagonize the ATAD5-mediated unloading of PCNA, which is consistent with our observation that PCNA unloading is slowed in Hat1 -/cells (79). Finally, the presence of Hat1 on nascent chromatin near replication forks suggests that Hat1 may directly modify and regulate components of the replisome.…”
Section: Discussionsupporting
confidence: 92%
“…Decreased levels of these proteins in the proximity of replication forks may create an altered chromatin structure that negatively affects replication fork function or they may be directly involved in replisome function. Indeed, it was recently shown that Brd2, Brd3 and Brd4 function at the replication fork to antagonize the ATAD5-mediated unloading of PCNA, which is consistent with our observation that PCNA unloading is slowed in Hat1 -/cells (79). Finally, the presence of Hat1 on nascent chromatin near replication forks suggests that Hat1 may directly modify and regulate components of the replisome.…”
Section: Discussionsupporting
confidence: 92%
“…3A). After 72 hours of knock down, we wealth of studies that established mechanisms of BRD4 in transcription regulation, and earlier work showing replication dysfunction caused by BRD4 loss 30,38,67,68 , we focused on the role of BRD4 in the prevention of TRC-induced DNA damage.…”
Section: Bet Protein Lossmentioning
confidence: 99%
“…If these roadblocks are not resolved, collisions with the replication machinery will lead to replication fork breakdown and DNA strand breaks. Important factors have been identified that prevent and resolve R-loops, including the RNAPII activator CDK9 and the RNA:DNA hybrid endonuclease RNase H1 [27][28][29][30][31][32][33][34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…In living cells many more proteins associate with replisomes than are required for “minimal” biochemical reconstructions 37,12 . These interactions may be constitutive or induced by replication stress, but are typically interpreted as representing a single complex (see Introduction) 15,22,3842 .…”
Section: Discussionmentioning
confidence: 99%
“…The identification and characterization of the minimal components of biochemically active replisomes, the result of decades of extraordinary work from multiple laboratories, necessarily reflects studies with deproteinized model DNA substrates under carefully controlled conditions. However, in vivo there are hundreds of replisome associated proteins 812 . Presumably this reflects the multiple layers of complexity that characterize replication of the genome in living cells.…”
Section: Introductionmentioning
confidence: 99%